Inhibition of retinoid X receptor improved the morphology, localization of desmosomal proteinsand paracellular permeability in three-dimensional cultures of mouse keratinocytes. (16th February 2022) - Ishikawa, Shoko; Nikaido, Misaki; Otani, Takahito; Ogata, Kayoko; Iida, Hiroshi; Inai, Yuko; Tamaoki, Sachio; Inai, Tetsuichiro
Abstract: Retinoic acid (RA) plays an important role in epithelial homeostasis and influences the morphology, proliferation, differentiation and permeability of epithelial cells. Mouse keratinocytes, K38, reconstituted non-keratinized stratified epithelium in three-dimensional (3D) cultures with serum, which contains retinol (a source of RA), but the morphology was different from in vivo epithelium. The formed epithelium was thick, with loosened cell–cell contacts. Here, we investigated whether the inhibition of RA receptor (RAR)/retinoid X receptor (RXR)-mediated signaling by an RXR antagonist, HX 531, improved K38 3D cultures in terms of morphology and intercellular junctions. The epithelium formed by 0.5 μM HX531 was thin, and the intercellular space was narrowed because of the restoration of the layer-specific distribution of desmoglein (DSG)-1, DSG3 and plakoglobin (PG). Moreover, the levels of desmosomal proteins and tight junction proteins, including DSG1, DSG2, DSG3, PG, claudin (CLDN)-1 and CLDN4 increased, but the adherens junction protein, E-cadherin, did not show any change. Furthermore, CLDN1 was recruited to occludin-positive cell–cell contacts in the superficial cells and transepithelial electrical resistance was increased. Therefore, K38 3D cultures treated with 0.5 μM HX531 provides a useful in vitro model to study intercellular junctions in the non-keratinized epithelium.